Penguatan Literasi Digital dan Sosialisasi Nomor Induk Berusaha Bagi Pelaku UMKM: Inovasi Mahasiswa PPM UIN Salatiga di Desa Jetis Bandungan - Asna, Royatul; Vidya Natasya, Adinda; Latif Ridwan, Muhammad; Muhammad Ramdani, Adji; Mubarok, Khoirul (Jurnal Pengabdian Multidisiplin dan Pemberdayaan Masyarakat, 2026)
The Micro, Small, and Medium Enterprises (MSME) sector is very important to the Indonesian economy. However,many MSMEs still face challenges, especially in the areas of digital literacy and business law. Many business owners lack official documentation due toa lack of understanding about the importance of the Business Identification Number (NIB), whileMSME products struggle to compete in the market due to a lack of expertise inutilizing digital technology. Students from UIN Salatiga implemented an NIB outreach programand computer literacy improvement program in Jetis Village, Bandungan District,Bandungan, Semarang Regency, as part of the Community Service Program(PPM). Through direct mentoring, observation, and interviews, this research used qualitative methodology with a Participatory Action Research (PAR) approach. The results of the activity show that MSMEs have begun touse digital platforms to help market their products and are increasingly aware of theimportance of the Business Identification Number (NIB) and the steps required toobtain it through the OSS system. In addition, several entrepreneurs whoreceived assistance from students successfully obtained their NIB. Throughthe formation of small support groups, this activity increased social solidarityamong MSMEs while also enhancing individual capacity. Thus, this programpromoted community economic independence and increased the competitiveness of MSMEs in Jetis Village.